2015
DOI: 10.1016/j.labeco.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Spillover effects of unionisation on non-members' wellbeing

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 45 publications
4
8
0
Order By: Relevance
“…Although these findings contradict our hypothesis, they are in line with some researchers (Haile et al, 2015) who found that unions often raise unfulfilled expectations.…”
Section: Drivers Of Intrapreneurshipsupporting
confidence: 83%
“…Although these findings contradict our hypothesis, they are in line with some researchers (Haile et al, 2015) who found that unions often raise unfulfilled expectations.…”
Section: Drivers Of Intrapreneurshipsupporting
confidence: 83%
“…The responses to these eight questions on domain satisfaction constitute the main outcome variables of interest to this paper. In addition, a summative measure of ‘overall’ job satisfaction has also been generated by recoding each of the eight facets of satisfaction into a (−2, 2) scales, where ‘−2’ is ‘very dissatisfied’ and ‘2’ is ‘very satisfied’, and summing across (see Bryson et al ., , , and Haile et al ., , for recent applications of this approach). The resulting single summative job satisfaction outcome measure, which is depicted in Figure , runs from −16 to 16.…”
Section: Data and Variablesmentioning
confidence: 99%
“…-Is the effect of trade union membership on job satisfaction for a particular employee affected by what colleagues do or, more generally, by social interactions (see Haile et al 2015)?…”
Section: Open Issuesmentioning
confidence: 99%